2005
DOI: 10.2174/1568014054065285
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Growth Factors in the Treatment of Osteoarthritis: What Could be the Best Disease Modifying Drugs

Abstract: Osteoarthritis (OA) is by far the most prevalent arthritic disease affecting around 10% of the world's population and approximately 60% of 60-year-olds. It is also one of the most common arthritic diseases seen by general practitioners and rheumatologists. The increased frequency of OA with age, makes it a growing social health concern, as it is a disease associated with disability and pain. In the US today, the immediate cost of the disease is estimated at approximately 60 billion dollars a year. Despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 154 publications
(185 reference statements)
0
5
0
Order By: Relevance
“…The functional limitation in the affected joint, which is caused by progressive degradation of cartilage and subchondral tissue remodeling, leads to bone deformity [ 1 ]. It is reported that metabolic interactions between cartilage and bones play pivotal roles in the pathogenesis of OA [ 2 ]. During OA progression, activated osteoblasts induce the production of matrix metalloproteinases (MMPs) by chondrocytes, which leads to cartilage degradation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functional limitation in the affected joint, which is caused by progressive degradation of cartilage and subchondral tissue remodeling, leads to bone deformity [ 1 ]. It is reported that metabolic interactions between cartilage and bones play pivotal roles in the pathogenesis of OA [ 2 ]. During OA progression, activated osteoblasts induce the production of matrix metalloproteinases (MMPs) by chondrocytes, which leads to cartilage degradation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The approach for treatment of OA is often multifaceted and relies upon disease‐modifying OA agents (Dieppe and Lohmander, 2005; Martel‐Pelletier et al., 2005). The major objective of treatment is to minimise joint pain by reducing the inflammation, as well as to slow the progression of the osteopathy.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the synthesis/action of proinflammatory cytokines can be down-regulated by either antiinflammatory cytokines, the release of soluble receptors, or natural antagonists (14). In recent years, the family of nuclear receptors, including peroxisome proliferatoractivated receptor ␥ (PPAR␥), has generated particular interest because of its potential role in regulating the synthesis of a large number of catabolic factors involved in arthritis.…”
mentioning
confidence: 99%